Proposed new interior design of Aspire Paradise Office for Aspire Paradise at Lot Pt 918/1006, Petaling Java Selatan, Daerah Petaling, Selangor Darul Ehsan/ Nur Shaqirin Syaiz Yusazudi - Yusazudi, Nur Shaqirin Syaiz (Faculty of Architecture, Planning and Surveying, 2012)
The plan is a powerful tools in the design process that requires both intellectual and creative rigor. All the design must be connected to the project that has been decided. Before making the design, majir aspect must be considered to get the information. The research, case study, design schemaic aand the planning have to be done to make sure that client will give the good reaction to our design. Because of that, the organized work must been done perfectly starting from the design development untill the end of the project. Proposed new interior design scheme of office for aspire paradise is one of it include what occur in client and customer need. It also requested to build a aspire paradise office do that can fill all customer and client needs.generally, aspire paradise need to share with their clients all of their products. At the same time they need to give comfort space and good facilities to customers. According to the objectives and the issues, a spce planning must be suitable with the design concept and images. So, to realize the design into space is a difficult way because it has the procedure that must be followed. The planning has been produced and the ideas that wanted to be applied into the space must be linked to the concept and images. By that, the good design is produced with the concept, the images, into the design axis and followed by the development of ideas. Guiding customer needs, design that will be molded are applying sustainable design and green design.